Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find [tex]\( g(f(x)) \)[/tex] for the given functions [tex]\( f(x) = x - 7 \)[/tex] and [tex]\( g(x) = 5x + 2 \)[/tex], we can follow these steps:
1. Find [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = x - 7 \][/tex]
2. Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex] to find [tex]\( g(f(x)) \)[/tex]:
Because [tex]\( g(x) \)[/tex] is given by [tex]\( g(x) = 5x + 2 \)[/tex], we substitute [tex]\( f(x) \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(f(x)) = g(x - 7) \][/tex]
3. Apply the function [tex]\( g \)[/tex] to [tex]\( (x - 7) \)[/tex]:
Substitute [tex]\( (x - 7) \)[/tex] into the expression for [tex]\( g(x) \)[/tex]:
[tex]\[ g(x - 7) = 5(x - 7) + 2 \][/tex]
4. Simplify the expression:
[tex]\[ g(x - 7) = 5(x - 7) + 2 = 5x - 35 + 2 \][/tex]
[tex]\[ g(x - 7) = 5x - 33 \][/tex]
Thus, the function [tex]\( g(f(x)) \)[/tex] can be written in the form:
[tex]\[ g(f(x)) = 5x - 33 \][/tex]
From this expression, we see that the coefficient of [tex]\( x \)[/tex] is [tex]\( 5 \)[/tex] and the constant term is [tex]\( -33 \)[/tex]. Therefore:
[tex]\[ g(f(x)) = 5x + (-33) \][/tex]
So, the coefficients are:
[tex]\[ g(f(x)) = 5x + (-33) \][/tex]
The coefficient of [tex]\( x \)[/tex] is [tex]\( 5 \)[/tex].
The constant term is [tex]\( -33 \)[/tex].
Thus, the function [tex]\( g(f(x)) \)[/tex] can be expressed as:
[tex]\[ g(f(x)) = 5x - 33 \][/tex]
1. Find [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = x - 7 \][/tex]
2. Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex] to find [tex]\( g(f(x)) \)[/tex]:
Because [tex]\( g(x) \)[/tex] is given by [tex]\( g(x) = 5x + 2 \)[/tex], we substitute [tex]\( f(x) \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(f(x)) = g(x - 7) \][/tex]
3. Apply the function [tex]\( g \)[/tex] to [tex]\( (x - 7) \)[/tex]:
Substitute [tex]\( (x - 7) \)[/tex] into the expression for [tex]\( g(x) \)[/tex]:
[tex]\[ g(x - 7) = 5(x - 7) + 2 \][/tex]
4. Simplify the expression:
[tex]\[ g(x - 7) = 5(x - 7) + 2 = 5x - 35 + 2 \][/tex]
[tex]\[ g(x - 7) = 5x - 33 \][/tex]
Thus, the function [tex]\( g(f(x)) \)[/tex] can be written in the form:
[tex]\[ g(f(x)) = 5x - 33 \][/tex]
From this expression, we see that the coefficient of [tex]\( x \)[/tex] is [tex]\( 5 \)[/tex] and the constant term is [tex]\( -33 \)[/tex]. Therefore:
[tex]\[ g(f(x)) = 5x + (-33) \][/tex]
So, the coefficients are:
[tex]\[ g(f(x)) = 5x + (-33) \][/tex]
The coefficient of [tex]\( x \)[/tex] is [tex]\( 5 \)[/tex].
The constant term is [tex]\( -33 \)[/tex].
Thus, the function [tex]\( g(f(x)) \)[/tex] can be expressed as:
[tex]\[ g(f(x)) = 5x - 33 \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.